Vanilla Cultivation in Southern Florida - Alan H. Chambers; Pamela Moon; Vovener Edmond; Elias Bassil (EDIS, 2019)
Vanilla extract is popular around the world as an ingredient in ice cream and various other desserts. The botanical source of vanilla extract is primarily the cured beans of Vanilla planifolia. The United States is the world?s largest importer of vanilla beans, but domestic production is minimal. However, southern Florida has a favorable growing environment for vanilla cultivation. This new 7-page publication of the UF/IFAS Horticultural Sciences Department includes information relevant to growers interested in establishing a vanillery. Written by Alan H. Chambers, Pamela Moon, Vovener de Verlands Edmond, and Elias Bassil. https://edis.ifas.ufl.edu/hs1348